Origin of green emission and charge trapping dynamics in ZnO nanowires - Li, Mingjie (2013)
The origins of the commonly observed green emission (GE) from ZnO nanostructures remain highly controversial despite extensive studies over the past few decades. Herein, through a comprehensive ultrafast optical spectroscopy study, new insights into its origin and the charge trapping dynamics at the GE centers in ZnO nanowires prepared by the vapor transport method are gained. Transient absorption spectroscopy (TAS) revealed a sub-band-gap absorption bleaching band arising from the state filling of the electrons in the conduction band and holes trapped in the GE centers. The GE originates from the recombination between the electrons in the conduction band and/or shallow donor levels and the holes trapped at the GE centers (which are located at ∼0.88 eV above the valence band). Importantly, an ultrafast excitonic Auger-type hole trapping process to the GE centers occurring in a subpicosecond time scale was also uncovered by TAS—shedding new light on the mechanism behind the fast and efficient charge trapping of photoexcited carriers. The knowledge gained is crucial for the development of ZnO-based optoelectronic devices.